A CAD-CAM prosthodontic option and gingival zenith position for a rotated maxillary right central incisor: An evaluation - Mukesh Singhal; Romil Singhal (Wolters Kluwer Medknow Publications, 2012)
Objective: Even with beautifully done restorations, an unattractive gingival zenith position, can negatively affect the smile of a person. In this short communication we describe the treatment of a rotated maxillary right central incisor using a digital photographic approach instead of the conventional approach. Background: The conjecture literature on prosthodontic considerations and gingival zenith position in cases of rotated maxillary central incisors is sparse. The gingival zenith level (GZL) in an apical-coronal direction of lateral incisors, relative to the gingival tangential zenith line joining the adjacent central incisor and canine, is approximately 1 mm under healthy conditions. Materials and Methods: For our patient, the treatment plan was decided by CAD-CAM technique as Zirconia, jacket crown. Clinical procedures included enameloplasty on the left central and right lateral maxillary incisors. Reduction of the rotated and crooked incisor was performed in the normal manner; periodontal plastic surgery was also done. Results: The patient expressed satisfaction with the intermediary (preliminary) two-dimensional photographs that were provided by the CAD-CAM system. The technique distinguished among the different treatment modalities for aesthetics and to relieve the emotional problems which were faced by female patient. The gingival zenith level of the rotated incisor was also improved. Conclusion: Digital imaging provides an immediate treatment option for the patients. Software also provides an interim aid, for the clinician as well as technician, in the form of two-dimensional photographs. CAD-CAM is entirely a helping instrument against the conservative prosthetic options and gingival zenith position for a rotated central incisor. It helps in patient education and in motivation.